EFFECT OF TIME AND FREQUENCY OF TOPPING ON STORAGE ROOT AND CUTTING PRODUCTION OF A BUSHY SWEET POTATO CULTIVAR - Villamayor Jr, Federico G.; Perez, Rudy D. (Annals of Tropical Research, 1988)
The effect of topping on storage root and apical stem cutting production of a bushy sweet potato cultivar (VSP-2) was studied. In the first experiment, all terminal cuttings at least 16 cm long were cut either at 38, 45, 52, or 59 days after planting (DAP). Storage root yield was not significantly affected by the time of topping. Meanwhile, the number of cuttings per plant (Y) is significantly related to the time of topping (X) by the equation Y = 0.31X - 9.58 at 1% level (r = 0.997) In the second experiment, the treatments were the frequencies of topping, i.e. one to five times. Topping started at 32 DAP and was repeatedly done at 2-week intervals depending on the topping frequency. Only terminal shoots reaching 25 cm long were cut. The number of cuttings produced per m² (Y) is significantly related to the frequency of topping (X) by the equation Y = 7.7X - 1.78 at 1% level (r = 0.988) On the other hand, topping significantly reduced yield. The total storage root yield in t/ha (Y) is also significantly related to the frequency of topping by the equation Y = 18.45 - 2.34X at 1% level (r = - 0.985).